RATIONALITY: A CENTRAL POINT BETWEEN TRADITIONAL FINANCE AND BEHAVIOURAL FINANCE - V.A., Subramaniam; T., Velnampy (International Journal of Research -GRANTHAALAYAH, 2017)
Investment plays an important role not only in the life of an individual but also in the development of countries. People save money for the purpose of future consumption and invest the saved money with the objectives of protecting the real value of money and making more money. Bodie, Kane & Marcus (1998) defined the term investment as the current commitment of money and other resources with the expectation of obtaining future benefits. Investment decision making is an important aspect in the process of investment, which relates with the selection of one or more investment options for investing the money.